Comparative Study of ɛ-Polylysine or Nisin Inhibition Kinetics of Lactococcus lactis and Spoilage Microorganisms in Fresh Flammulina velutipes Fruiting Bodies. (1st March 2022) - Wei, Qi; Pan, Xinyuan; Jia, Zhen; Li, Changcheng; Chen, Bingzhi; Fang, Ting; Jiang, Yuji
Abstract : Flammulina velutipes is one of the most important edible mushrooms, which quickly decays with a short shelf life. However, little is known about the effect of ɛ -polylysine ( ɛ -PL) or nisin on the survival of Lactococcus lactis ( L. lactis ) during the storage at constant temperatures. The objective of this study was to investigate the effect of ɛ -PL or nisin on the growth of L. lactis and background (BK) microorganisms in fresh Flammulina velutipes fruiting bodies (FVFB) and develop mathematical models to predict their growth behavior. The effect of ɛ -PL (0.15 and 0.30 g/kg) or nisin (0.10 and 0.20 g/kg) on the growth of L. lactis and BK microorganisms in FVFB was analyzed at 4, 16, and 20°C. The lag phase of L. lactis was extended, and the specific growth rate was decreased by increasing concentrations of ɛ -PL or nisin and lowering the temperature. The results showed that ɛ -PL or nisin could control the growth of L. lactis in FVFB. However, the growth of BK microorganisms was not affected by ɛ -PL or nisin. The growth of L. lactis and BK microorganisms could be successfully described by the reparameterized Gompertz and no lag phase models, respectively. Additionally, ɛ -PL or nisin could maintain the quality of FVFB by preventing weight loss, color-changing, and decreasing soluble solid content in FVFB at 4°C. These results suggest that ɛ -PL or nisin in combination with low temperature may inhibit the growth of L. lactis in FVFB and prevent the decrease in the quality of FVFB.